Efektivitas Pelatihan Augmented Reality Berbasis Project-Based Learning Untuk Meningkatkan Keterampilan Digital Siswa SMK - Muhammad Ruslan Maulani; Santoso Santoso (Jurnal Medika: Medika, 2026)
Vocational high school (SMK) students, despite being adept technology consumers, often face a "productive digital skills gap." They have not been empowered to become content creators, and smartphone use in schools remains sub-optimal for learning. This community service (PkM) aims to enhance students' productive digital skills by transforming their role from passive consumers to creators. The specific objective is to measure the effectiveness of Augmented Reality (AR) learning media creation training implemented using the Project-Based Learning (PBL) method. The method involved intensive training and mentoring with 30 students from SMK Daarut Tauhid (TKJ department). Effectiveness was measured using a one-group pre-test/post-test design, with competency data analyzed using the N-Gain Score. The usability of the student-developed products was tested using the System Usability Scale (SUS). The results demonstrated a highly significant improvement in competence. The average pre-test score (38.50) increased dramatically to 84.75 on the post-test. The N-Gain analysis yielded a score of 0.752, which falls into the "High" effectiveness category. Furthermore, 100% of the groups successfully created functional AR prototypes, with the best product achieving a SUS usability score of 79.5 ("Good"). It is concluded that PBL-based AR training is highly effective in improving the productive digital skills of vocational students and shifting their mindset from passive consumers to technology creators.